2013
DOI: 10.1097/grf.0b013e31827feea4
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Abstinence Syndrome

Abstract: Recent rise in rates of opiate replacement therapy among pregnant women have resulted in increasing number of infants requiring treatment for neonatal abstinence syndrome. Short- and long-term developmental outcomes associated with prenatal opiate exposure are discussed, including symptoms and severity of neonatal abstinence syndrome (NAS), and early cognitive and motor delays. Maternal and infant risk factors are discussed, and include patterns of maternal substance use during pregnancy, genetic risk, polysub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(53 citation statements)
references
References 30 publications
0
48
0
3
Order By: Relevance
“…A clinical diagnosis of depression or anxiety is often preceded by motor, cognitive, sleep and behavioral problems in early childhood and adolescence (Kelly, Day, & Streissguth, 2000; Logan, Brown, & Hayes, 2013a; Nanson & Hiscock, 1990; Streissguth et al, 2004). These behavioral issues, including attention and social deficits, impulsivity, hyperactivity, and anxiety, may be associated with stress hyper-responsiveness and circadian disruptions (Gruber, Sadeh, & Raviv, 2000; McClung, 2013; Sher, 2003; Verma, Hellemans, Choi, Yu, & Weinberg, 2010).…”
Section: The Effects Of Drugs Of Abuse On Circadian Rhythms and Circamentioning
confidence: 99%
“…A clinical diagnosis of depression or anxiety is often preceded by motor, cognitive, sleep and behavioral problems in early childhood and adolescence (Kelly, Day, & Streissguth, 2000; Logan, Brown, & Hayes, 2013a; Nanson & Hiscock, 1990; Streissguth et al, 2004). These behavioral issues, including attention and social deficits, impulsivity, hyperactivity, and anxiety, may be associated with stress hyper-responsiveness and circadian disruptions (Gruber, Sadeh, & Raviv, 2000; McClung, 2013; Sher, 2003; Verma, Hellemans, Choi, Yu, & Weinberg, 2010).…”
Section: The Effects Of Drugs Of Abuse On Circadian Rhythms and Circamentioning
confidence: 99%
“…Morphine and methadone are considered the two standard of care options for first-line treatment, with on-going clinical trials to determine best practice and long-term outcomes (Backes et al, 2012; Brown et al, 2014; Hall et al, 2014; Hudak et al, 2012; Lee et al, 2015; Sarkar et al, 2006). Approximately 25% of infants have a particularly severe course of withdrawal, requiring adjunctive medication therapy in addition to first-line opioid replacement – most typically a barbiturate (phenobarbital) or a sympatholytic (clonidine; Jansson et al, 2009; Jones et al, 2010; Logan et al, 2013). Infants with this more severe phenotype of NAS typically have a longer duration of pharmacologic treatment with associated longer inpatient hospitalization (Wachman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These studies have found that prenatal cocaine exposure is related to problems with sustained attention and behavioral self-regulation even after controlling for covariates (Ackerman et al, 2010). However, there have been relatively few studies of opioid and poly-substance exposure (Lester & Lagasse, 2010;Logan, Brown, & Hayes, 2013).…”
mentioning
confidence: 99%
“…Some studies find that young children who have been exposed to opioids and multiple substances have greater impairments in general cognitive abilities than non-exposed children (Bunikowski et al, 1998;Hunt et al, 2008;Johnson, Diano, & Rosen, 1984;Logan et al, 2013;Moe, 2002a;Moe & Slinning, 2001;Salo et al, 2009;van Baar & de Graaff, 1994;Wahlsten & Sarman, 2013;Wilson, 1989;Wilson, McCreary, Kean, & Baxter, 1979), whereas others do not find such differences either before (de Cubas & Field, 1993;Kaltenbach & Finnegan, 1989;Melinder et al, 2013;Rosen & Johnson, 1985;Strauss, Lessen-Firestone, Chavez, & Stryker, 1979) or after controlling for covariates (Bauman & Levine, 1986;Lifschitz, Wilson, Smith, & Desmond, 1985;Messinger et al, 2004).…”
mentioning
confidence: 99%